Surgical site infections following instrumented stabilization of the spine - Dapunt, Ulrike A.; Günther, Frank; Pepke, Wojciech; Hemmer, Stefan; Akbar, Michael (Therapeutics and clinical risk management, 2017)
Background: Implant-associated infections are still a feared complication in the field of orthopedics. Bacteria attach to the implant surface and form so-called biofilm colonies that are often difficult to diagnose and treat. Since the majority of studies focus on prosthetic joint infections (PJIs) of the hip and knee, current treatment options (eg, antibiotic prophylaxis) of implant-associated infections have mostly been adapted according to these results. Objective: The aim of this study was to evaluate patients with surgical site infections following instrumented stabilization of the spine with regard to detected bacteria species and the course of the disease. Patients and methods: We performed a retrospective single-center analysis of implant-associated infections of the spine from 2010 to 2014. A total of 138 patients were included in the study. The following parameters were evaluated: C-reactive protein serum concentration, microbiological evaluation of tissue samples, the time course of the disease, indication for instrumented stabilization of the spine, localization of the infection, and the number of revision surgeries required until cessation of symptoms. Results: Coagulase-negative Staphylococcus spp. were most commonly detected (n=69, 50%), followed by fecal bacteria (n=46, 33.3%). In 23.2% of cases, no bacteria were detected despite clinical suspicion of an infection. Most patients suffered from degenerative spine disorders (44.9%), followed by spinal fractures (23.9%), non-degenerative scoliosis (20.3%), and spinal tumors (10.1%). Surgical site infections occurred predominantly within 3 months (64.5%), late infections after 2 years were rare (4.3%), in particular when compared with PJIs. Most cases were successfully treated after 1 revision surgery (60.9%), but there were significant differences between bacteria species. Fecal bacteria were more difficult to treat and often required more than 1 revision surgery. Conclusion: In summary, we were able to demonstrate significant differences between spinal implant-associated infections and PJIs. These aspects should be considered early on in the treatment of surgical site infections following instrumented stabilization of the spine. Keywords: surgical site infection, biofilm infection, instrumentation of the spine, coagulase-negative Staphylococci